High-resolution isotope dietary analysis of Mesolithic and Neolithic humans from Franchthi Cave, Greece - Valentina Martinoia; Anastasia Papathanasiou; Sahra Talamo; Rebecca MacDonald; Michael P. Richards (PLoS ONE, 2025)
Franchthi Cave, in the Greek Peloponnese, is a well-known Paleolithic, Mesolithic and Neolithic site, with several human burials. In many parts of Europe there is clear evidence from archaeological and isotopic studies for a diet change between the Mesolithic and Neolithic periods. This is especially the case in coastal contexts where there is often a shift from predominantly marine food diets in the Mesolithic to terrestrial (presumably domesticated) foods in the Neolithic. However, at Franchthi Cave previous isotope research did not show changes in diets between these two periods, and also showed relatively little input from marine foods in diets in either time period, despite the coastal location of the site and the presence of marine shellfish and fish, including tuna. High-resolution compound specific amino acid isotope analysis reported here from humans from the Lower Mesolithic and Middle Neolithic periods confirms the previous bulk isotope results in showing little or no consumption of marine foods in either time period. However, it is important to note that our isotopic sample does not come from episodes when tuna is abundant and therefore do not cover the whole range of known diets from the site. Conversely, in our sample there is some evidence of marine food consumption (likely seaweed) by sheep in the Neolithic period. We also report here five direct AMS radiocarbon dates for the five analyzed humans from the site.